Can virtual reality simulation prepare patients for an MRI experience?. Issue 3 (August 2020) - Nakarada-Kordic, I.; Reay, S.; Bennett, G.; Kruse, J.; Lydon, A.-M.; Sim, J.
Abstract: Introduction: A Magnetic Resonance Imaging (MRI) examination is often described by patients as frightening and uncomfortable. To prepare patients for an MRI examination, this study explored the use of virtual reality (VR) simulation compared to a mock MRI scan (full-scale MRI machine replica, without internal magnets). Methods: Twenty participants underwent a VR and a mock MRI scan. Ratings of anxiety and how comfortable and relaxed the participants felt were recorded at five touchpoints during and after each simulation. Post-simulation questionnaires were used to gather responses on the experience and preferences. Results: No significant differences were found in participants' ratings of how anxious they felt during or between the two simulations (χ2 (9) = 27.269, p = .126), or how relaxed they felt (χ2 (9) = 14.664, p = .101). There were also no significant differences in the reported levels of comfort between the two types of simulation (χ2 (9) = 20.864, p = .013, post hoc tests for all VR versus mock scan rankings p > .05). There were no significant differences in how real the participants thought each simulation felt, or how anxious, relaxed, and comfortable they felt following each type of simulation (p > .05). Although 65% of participants thought the mock simulation felt more real than the VR, 86% found VR simulation to be a helpful way to prepare for a real MRI exam. Conclusion: VR could be a feasible and accessible alternative to mock scanning. It has the potential to improve patient experiences of potentially stressful MRI examinations. Implications for practice: VR offers clinicians a new cost-effective tool to prepare patients for an MRI examination. VR technology could be used at home, as a training tool, to familiarise clinicians and clinical trainees with the MRI procedure and better understand patients' experiences.